Teaching Catholic Religion in Croatian Public Schools: Legal Frame and Challenges - Quirós-Fons, Antonio (Religions, 2024)
This paper explores the Croatian framework of collaboration between the state and the Catholic Church in the educational field, specifically the teaching of Catholic religion in public schools. First, the statute of the subject of religion was analyzed, following what is established in the Agreement with the Holy See and its Development Agreement with the Croatian Conference of Bishops. Some challenges to this peculiar model of cooperation were revised, mainly the ones regarding the enrollment and the co-responsibility of both ecclesiastical and state authorities in the approval and control of programs and contents. Second, the status of religion teachers was also evaluated. The same ecclesiastical and state authorities also have competence over the teaching staff, from their training to the control of their work, and must confront inconvenient situations related to the suitability of these professionals. In the study of each section and its corresponding rules and practices, it was possible to outline singular aspects, in some cases recognized—or rejected—judicially as discriminatory. This approximation to the right to religious education intends to examine the practice observed by the respective authorities in applying such provisions. The obtained findings and proposals about the singular Croatian model provide a useful contribution for comparative purposes.